Effectiveness of an oral care tablet containing kiwifruit powder in reducing oral bacteria in tongue coating: A crossover trial. Issue 2 (3rd December 2019) - Matsumura, Yuki; Hinode, Daisuke; Fukui, Makoto; Yoshioka, Masami; Asakuma, Hiroki; Takii, Hiroshi
Abstract: Objectives: The aim of this study was to investigate the effect of an oral care tablet containing kiwifruit powder on oral bacteria in tongue coating compared with tongue brushing. Material and methods: Thirty‐two healthy, young adults were enrolled, and a crossover clinical trial was conducted. The volatile sulfur compound (VSC) concentration, Winkel tongue‐coating index (WTCI), and the number of total bacteria in addition to Fusobacterium nucleatum in tongue coating were measured. We instructed subjects to remove tongue coating by tongue brush for Intervention I, to keep the oral care tablet containing kiwifruit powder on the tongue dorsum and to let it dissolve naturally for Intervention II, and three oral care tablets 1 day before the measurement for Intervention III. Results: There were significant differences in terms of the level of H2 S, VSC, and WTCI at Intervention I and all evaluation values at Intervention II. There were significant differences in terms of the level of H2 S, VSC, WTCI, the number of total bacteria, and F. nucleatum at Intervention III. The value of WTCI, the number of bacteria, and F. nucleatum decreased significantly after taking the oral care tablets than after tongue brushing. When compared with Interventions I and III, Intervention III showed the effective results; there were significant differences in the number of total bacteria and F. nucleatum between tongue brushing and taking tablets. Conclusions: These results suggested that the oral care tablet containing kiwifruit powder could be effective in reducing total bacteria and F. nucleatum in tongue coating when compared with tongue brushing.